2018
DOI: 10.1186/s12966-018-0758-1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and cost-effectiveness of a loyalty scheme for physical activity behaviour change maintenance: results from a cluster randomised controlled trial

Abstract: BackgroundWe evaluated the effectiveness and cost-effectiveness of a loyalty scheme based intervention involving rewards for increasing physical activity in public sector employees.MethodsA cluster randomised wait-list controlled trial in public sector organisations in Northern Ireland. We randomly assigned clusters (1:1) using a computer generated random sequence. Researchers were masked to allocation, but participants were not. Employees aged 18–65 years with no self-reported medical contraindications to phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 24 publications
0
39
1
3
Order By: Relevance
“…A study amongst employees with mixed professions who participated in a similar counselling intervention on physical activity, with one group only receiving counselling and another group receiving counselling and fitness testing, also showed no effects on physical activity compared to a control group (27). A recent study on a 6-month workplace intervention with a different approach, studying a loyalty scheme with financial incentives, also did not show a significant improvement in physical activity (28).…”
Section: Comparison With Other Studiesmentioning
confidence: 95%
See 1 more Smart Citation
“…A study amongst employees with mixed professions who participated in a similar counselling intervention on physical activity, with one group only receiving counselling and another group receiving counselling and fitness testing, also showed no effects on physical activity compared to a control group (27). A recent study on a 6-month workplace intervention with a different approach, studying a loyalty scheme with financial incentives, also did not show a significant improvement in physical activity (28).…”
Section: Comparison With Other Studiesmentioning
confidence: 95%
“…Different from previous studies (27)(28)(29)(30), our aim was to increase physical activity or reduce sedentary behaviour in order to improve mental health and cognition (16). Therefore, how the intervention was presented to participants may have altered their attitudes or behaviours.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…c ANCOVA comparison between 6-month means in the intervention group vs. 6-month means in the control group adjusted for baseline values of the outcome, randomisation stratum and season, and corrected for clustering. Reproduced with permission from Hunter et al 48 This article is distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/ licenses/by/4.0/), which permits unrestricted use, distribution, and reproduction in any medium, provided you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license, and indicate if changes were made. The Creative Commons Public Domain Dedication waiver (http://creativecommons.org/publicdomain/zero/1.0/) applies to the data made available in this article, unless otherwise stated.…”
Section: Exploratory Subgroup Analysesmentioning
confidence: 99%
“…48 This article is distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/), which permits unrestricted use, distribution, and reproduction in any medium, provided you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license, and indicate if changes were made. The Creative Commons Public Domain Dedication waiver (http://creativecommons.org/publicdomain/zero/1.0/) applies to the data made available in this article, unless otherwise stated.RESULTS FROM THE HEALTH ECONOMICS ANALYSISNIHR Journals Library www.journalslibrary.nihr.ac.uk pairs of cost difference and QALY difference Point estimate of ICER (cost difference = £25.85, QALY difference = -0.00009, ICER = -£290,178/QALY gained) Threshold at £20,000/QALY gained Threshold at £30,000/QALY gained Cost-effectiveness plane representing 1000 bootstrapped cost difference and QALY difference pairs.…”
mentioning
confidence: 99%
“…People who work in predominantly office-based occupations tend to spend a large part of their day inactive, and public organizations have been shown to have higher sickness absenteeism rates than private sector organizations (Black, Frost, & Frost, 2011;Hamilton, Hamilton, & Zderic, 2007). For example, whilst our objective measure of physical activity behavior (pedometer steps/day) indicated that participants assigned to both the intervention and control groups had a fairly high level of baseline physical activity, over 50% of participants were categorized as having 'low' physical activity levels according to self-reported General Physical Activity Questionnaire (GPAQ) (Hunter et al, 2019(Hunter et al, , 2018. However, evidence regarding the effectiveness of workplace physical activity interventions is mixed especially for long-term behavior change (Hutchinson & Wilson, 2012;Malik, Blake, & Suggs, 2014).…”
Section: Introductionmentioning
confidence: 98%